Theoretical and experimental investigation of secondary electron emission characteristics of MgO coating produced by atomic layer deposition. Issue 6 (15th April 2020) - Guo, Junjiang; Wang, Dan; Wen, Kaile; Xu, Yantao; Zhu, Xiangping; Liu, Lutao; Cao, Weiwei; Si, Jinhai; Lu, Min; Guo, Haitao
Abstract: Atomic layer deposition (ALD) is utilized to prepare thin MgO coatings 1–50 nm on Si substrate. In addition, secondary electron emission (SEE) coefficient of MgO/Si double-layered structure is evaluated as a function of coating thickness and primary electron (PE) energy. After neutralizing the surface of test specimen, we have accurately analyzed the relationship between secondary electron yield (SEY) of MgO coating and PE energy. Meanwhile, SEE characteristics of MgO/Si double-layered structure have been systematically analyzed. A maximum SEY value of 6.15 has been achieved at coating thickness of 30 nm and PE energy of 550 eV. Furthermore, theoretical model is established by using Dionne's SEE model to analyze experimentally measured SEY data, demonstrating consistency between experimentally measured and theoretically calculated results. This work demonstrates that SEE level of MgO coating can be optimized by tuning coating thickness and presents novel insights into SEE characteristics of composite materials. Those results can serve as a baseline for further design and fabrication of a wide array of electronic devices.